1993
DOI: 10.1099/00221287-139-6-1219
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of an endoglucanase and a cellodextrinase gene in Ruminococcus flavefaciens FD-1

Abstract: A gene which encodes a 35 kDa protein with both carboxymethylcellulase and xylanase activity was cloned from RuminococcusJEavefaciens FD-1 and the nucleotide sequence determined. The FD-1 gene, cell?, and the ceZA gene, which encodes a cellodextrinase, were used as probes to analyse transcription in R. flavefaciens grown under different conditions. Transcription of both genes was induced when cellulose was added to cells growing in cellobiose. This induction continued after cellulose depletion and after cell d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
20
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
4
20
0
Order By: Relevance
“…Moreover, it was reported that Clostridium thermocellum assimilates cellopentaose preferentially during growth on cellulose (57). In addition, the transcription of endoglucanase genes is induced by cellotriose rather than cellobiose in Ruminococcus flavefaciens (56). These findings indicate the presence of selective assimilation and response mechanisms for specific cellooligosaccharides in these bacteria.…”
mentioning
confidence: 56%
“…Moreover, it was reported that Clostridium thermocellum assimilates cellopentaose preferentially during growth on cellulose (57). In addition, the transcription of endoglucanase genes is induced by cellotriose rather than cellobiose in Ruminococcus flavefaciens (56). These findings indicate the presence of selective assimilation and response mechanisms for specific cellooligosaccharides in these bacteria.…”
mentioning
confidence: 56%
“…Doerner et al (164) have reported that the celA and celC genes were expressed constitutively while expression of the celB and celD was induced by cellulose. However, Wang et al (721) have reported that the cellodextrinase celA and celE genes are both induced by cellulose.…”
Section: Molecular Biology Of Cellulase Enzymesmentioning
confidence: 99%
“…On the other hand, there are many reports of single-domain endoglucanases from R. flavefaciens and R. albus that are smaller than 50 kDa (30,33,40,41,42). This may suggest that not all cellulases are cellulosome associated in ruminococci.…”
Section: Discussionmentioning
confidence: 92%